Run for your life - Cucuzzella, Mark (Alfred A. Knopf, 2018)
"The first running book by a world's leading pioneering running doctor and athlete, creator of the Air Force's Efficient Running program--the result of more than three decades of study, practice, and science that shows us in clearly illustrated and accessible text how easy it is to run efficiently and injury-free, whether you're in your 20s, 60s or 70s; for beginning runners and experienced marathoners. In Run for Your Life, Dr. Mark Cucuzzella explains the simple mechanics of how our bodies have evolved and adapted to run. Despite our natural ability and our human need to run, each year more than half of all runners suffer injuries. Pain and discouragement inevitably follow. Cucuzzella's book outlines the proven, practical techniques to avoid injury and reach the goal of personal fitness and overall health. His book--the first running book to be written by a Professor of Medicine with the credibility of the Air Force behind him--gives us a straightforward, easy-to-follow look at the anatomy, bio-mechanics, nutrition, and/or clinical medicine with clear drawings and black-and-white photographs. The book provides illustrated exercises designed to teach healthy running, along with simple progressions, a weekly/monthly schedule detailing common mistakes and cautions that allow the reader to tailor the training regime to individual needs and abilities. With corresponding online videos and other innovative, book-Internet links"--